2019
DOI: 10.3390/microorganisms7100440
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: A Potential Result from the Collusion between Gut Microbiota and Mucosal Immune System

Abstract: Host health depends on the intestinal homeostasis between the innate/adaptive immune system and the microbiome. Numerous studies suggest that gut microbiota are constantly monitored by the host mucosal immune system, and any slight disturbance in the microbial communities may contribute to intestinal immune disruption and increased susceptibility to inflammatory bowel disease (IBD), a chronic relapsing inflammatory condition of the gastrointestinal tract. Therefore, maintaining intestinal immune homeostasis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 180 publications
(215 reference statements)
1
51
0
2
Order By: Relevance
“…It is widely accepted that TLR4 is a double-edged sword, as minor activation of TLR4 is essential in the maintenance of immune homeostasis, while excessive TLR4 activation can lead to the induction of host inflammatory responses (Steimle et al, 2019). TLR4 is highly expressed in the colon tissues of UC patients and DSS-induced colitic mice, and is considered to be a contributing factor to the initiation and development of intestinal inflammation in UC (Taniguchi et al, 2009;Murad, 2014;Yue et al, 2019). We found that the protein expression levels of TLR4, MyD88, p-p65, and p-IκBα were significantly increased in DSSinduced colitic mice; however, the expression levels of TLR4 and its downstream proteins were markedly decreased by obacunone treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely accepted that TLR4 is a double-edged sword, as minor activation of TLR4 is essential in the maintenance of immune homeostasis, while excessive TLR4 activation can lead to the induction of host inflammatory responses (Steimle et al, 2019). TLR4 is highly expressed in the colon tissues of UC patients and DSS-induced colitic mice, and is considered to be a contributing factor to the initiation and development of intestinal inflammation in UC (Taniguchi et al, 2009;Murad, 2014;Yue et al, 2019). We found that the protein expression levels of TLR4, MyD88, p-p65, and p-IκBα were significantly increased in DSSinduced colitic mice; however, the expression levels of TLR4 and its downstream proteins were markedly decreased by obacunone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The possible etiology of UC is complex and multifactorial including genetic, immune, microbiological, and environmental factors, each of which may lead to the occurrence of UC (Bernstein, 2017). Although the exact cause of UC remains unclear, accumulating evidence has indicated that interaction between mucosal immunity and gut microbiota plays a key role in the pathogenesis of UC (Yue et al, 2019). Additionally, clinical studies have indicated that the composition of three major phyla of bacteria present in the gut microbiota of UC patients is disturbed, with a decrease in the proportion of Firmicutes and Bacteroidetes and an increase in that of Proteobacteria (Matsuoka and Kanai, 2015;Mirsepasi-Lauridsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, multiple studies have demonstrated how microbiota composition in gut, lungs and skin impacts the clinical evolution of various pathologies, including inflammatory, autoimmune and behavioral disorders as well as infectious diseases [35][36][37][38][39][40]. In this multicenter study, we investigated the composition of sputum microbiota in TB disease and during anti-TB treatment.…”
Section: Rationale and Aim Of The Workmentioning
confidence: 99%
“…The pathogenesis of IBD involves a combination of dysfunctional innate and adaptive immunity, defective intestinal epithelial barrier, and imbalanced intestinal microbiota, causing chronic relapsing inflammatory disorder of the intestine [ 121 , 122 ]. CD is thought to be mainly driven by a T H 1 response, while UC is associated with a T H 2 response [ 122 , 123 ].…”
Section: Vitamin D and Immune-related Diseasesmentioning
confidence: 99%